2019
DOI: 10.1053/j.semtcvs.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Serum Troponin Trends in Infants Undergoing Cardiac Surgery

Abstract: Troponin-I (TN-I) levels are elevated following pediatric cardiac surgery with speculation that particular patterns may have prognostic significance. There is lack of procedure-specific data regarding postoperative TN-I levels in infants undergoing cardiac surgery. We hypothesized that TN-I elevation varies with type of surgery and persistent elevation predicts poor prognosis. We prospectively measured serial TN-I levels (preoperatively, 4, 8, 12, 24, and 48hours postoperatively) in 90 infants (age < 1 year) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…An important observation in the study was that the level of the 24-hour troponin measurements showed a decrement from that of the 4-hour troponin measurement in all of the cases except one. (Su et al, 2019) also found the same result; the troponin T tends to decrease gradually from the 4-hour and on after the operation.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…An important observation in the study was that the level of the 24-hour troponin measurements showed a decrement from that of the 4-hour troponin measurement in all of the cases except one. (Su et al, 2019) also found the same result; the troponin T tends to decrease gradually from the 4-hour and on after the operation.…”
Section: Discussionsupporting
confidence: 57%
“…The relation between troponin levels and the type of surgery showed statistically higher levels in TOF cases, and about 50% of TOF surgeries had troponin levels between 2 and 4 ng/ml. It is stated that high troponin is associated with complex congenital heart surgery (Su et al, 2019;Wada et al, 2018). Moderately positive, statistically significant correlations for both 4-and 24-hour troponin levels were detected with CPB, ACC, and operation durations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al and Liu et al observed the nadir of cardiac output, the minimal central venous oxygen saturation, and the peak of BNP and lactate level at 8h after the surgery ( 22 , 37 ). Su et al revealed that the increase of troponin-I beyond 8h after CPB was a strong predictor of postoperative hypoperfusion in infants ( 38 ).…”
Section: Discussionmentioning
confidence: 99%